Interleukin-4 prevents increased endothelial permeability by inducing pericyte survival and modulating microglial responses in diabetic retinopathy - Yun, Jang-Hyuk (Frontiers in Endocrinology, 2025)
IntroductionRetinal vascular leakage due to increased endothelial permeability is a major contributor to the pathogenesis of diabetic retinopathy (DR) and visual impairment. Pericyte loss and microglia-mediated inflammation exacerbate this vascular dysfunction. Interleukin-4 (IL-4) is known for its anti-inflammatory and tissue-protective properties, but its role in DR remains unclear. MethodsWe evaluated IL-4 expression and signaling in the retinas of streptozotocin-induced diabetic mice. In vitro assays were conducted under high-glucose and TNF-α conditions using retinal endothelial cells, pericytes, and microglia to assess IL-4’s effects on barrier function, cell viability, and inflammatory state. Pathway-specific analyses were performed to investigate PI3K/AKT and STAT6 signaling. ResultsIL-4 expression and downstream signaling were significantly reduced in diabetic retinas. IL-4 promoted pericyte survival via PI3K/AKT activation and modulated microglial functional profiles through STAT6 signaling, favoring an anti-inflammatory phenotype. These effects contributed to restored endothelial barrier integrity and tight junction protein expression under diabetic stress conditions in vitro. ConclusionIL-4 supports retinal vascular stabilization in DR by preserving pericyte viability and modulating microglial activity. These findings highlight IL-4 as a potential therapeutic target for preventing or slowing DR progression and warrant further preclinical investigation.